Inquiry and Accounting: Alternate Methods and Research Perspectives (Book). - Brief, Richard P.; Power, Michael (The Accounting Review, 1989)
Reviews the book "Inquiry and Accounting: Alternate Methods and Research Perspectives," by Ahmed Belkaoui.